Improvement of viscoelastic, elastic and plastic properties of Poly(L-lactide)/Graphene Oxide-Graft-Poly(L-lactide) nanocomposites by modulation of grafted chain length. (20th October 2020) - Campos, João M.; del Río, Benito; Lorenzo, Vicente; Ania, Fernando; Barros-Timmons, Ana; Ribeiro, M. Rosário
Abstract: The full potential of poly( L -lactide) (PLLA) reinforced with graphene oxide, GO, nanocomposites tends to be hindered by aggregation of the nanofillers. In order to promote a good dispersion of GO in the PLLA matrix, polymer grafting techniques have been explored to anchor PLLA onto functionalized GO surface to produce GO-PLLA hybrids. For this purpose, PLLA with a terminal triple bond was synthesized by ring-opening polymerization. By controlling the concentration of monomer to initiator, PLLA samples with three different chain lengths have been prepared and later coupled to azide-functionalized GO using click chemistry. These hybrids were then mixed with commercial PLLA and cast films have been prepared. The ensuing nanocomposite films were studied using Depth Sensing Indentation and the results have shown that PLLA matrix-filler interaction can be modulated by controlling the chain length of PLLA graft. This is a critical point because the enhancement of these interactions provides a stronger matrix-filler interphase which improves the stress transfer between both phases and increases the contribution of the interphase to the stiffening of the nanocomposites. Therefore, it has been proven that judicious functionalization of GO is an effective procedure for improving the strength, the stiffness and the creep resistance of the PLLA composites. Graphical abstract: